DISKRESI KEPOLISIAN DALAM PENGGUNAAN SENJATA API PERSPEKTIF HUKUM ISLAM (STUDI KASUS POLRESTABES MAKASSAR) - Putra, Wiyari Dwi; Ridwan, Saleh Ridwan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2020)
This research aims to answer how the rule of law and the application of police discretion in the use of firearms at the Makassar Police Headquarters. What is the view of Islamic law in responding to police discretion? The results of this study indicate that: The work of the police everywhere is to maintain law and public order, especially in terms of fighting crime in the community. Even though his duties and powers have been clearly defined by legal procedures, at the same time he is faced with a situation to make decisions that are according to his own judgment, and sometimes this is not in accordance with the applicable legal rules. because if one of them is done based on the rule of law then the other rules and order will be disturbed. Ijtihad and Discretion both have a strong legal basis but the legal position of the implementation of Ijtihad and Discretion has differences. In Ijtihad, if the ijtihad is right then it gets two rewards, and if one gets one reward. Whereas in the application of Discretion, if it is not correct or wrong in giving Discretion, then the Police Member shall bear the legal consequences of giving the Discretion. The implication of this research is that it is hoped that the application of Discretion within the scope of the Indonesian National Police in exercising their authority must act according to applicable regulations and are truly in the interests of police duties and public security. The public should know that the use of firearms is not arbitrarily used by the police outside of the provisions of the law. Keywords: Discretion; Police Cases; Firearms Users; Islamic Law Perspective;